What Do We Choose to Fly with Low-Cost Airlines: Thais’ Passenger Perspective - Reginio, Marianne; Kankaew, Kannapat (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
Generally, the price mechanism is the primary factor attracting customer choosing to fly. However, the other service components could not be neglected especially punctuality and service quality. This study aims to investigate the service components that enhance passenger return intention using of three low-cost airlines operating in Don Mueang International Airport (DMK), Thailand. The quantitative approach was employed by f-test to compare three airlines’ service components. Thereafter, the structural equation modelling was tested for the causal relation of the factors affecting passengers’ choice. The questionnaires were distributed to 1200 passengers who experienced flying with low-cost airlines. The results disclosed that there were differences among airlines namely; reliability, assurance, and the quality of products and services. Whereas, the most significant of passengers’ choices were reliability, assurance, and empathy.